Secular change of tectonic setting in the Archean Takanen greenstone belt, northeastern Karelia Province, Fennoscandian Shield - Järvinen, Ville; Karampelas, Nikolaos; Rämö, O. Tapani; Halkoaho, Tapio; Törmänen, Tuomo; Mikkola, Perttu; Lahaye, Yann (Geological Society of Finland, 2024)
Peer reviewed